Spin Isotope Separation Under Incomplete Carbon Oxidation in a Low-Temperature Plasma in an External Magnetic Field - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Khan V. A. Valery Alekseevich; Plekhanov V. G. Vladimir Georgievich; Izhoykin D. A. Dmitry Aleksandrovich; Bespala E. V. Evgeniy (Evgeny) Vladimirovich (2015, 2015)
Title screen